Multilingualism in Nortwestern part of Croatia during Habsburg rule - Jernej, Mirna (Array, 2012)
ers as a complex which reflects primarily cultural, but also political and social phenomena. This paper investigates these phenomena in the Northwestern part of Croatia under Habsburg rule and gives an overview of the discursive practices in the mentioned area and period of time. The concept of language contact includes not only the process of contact of various languages, but also the result of influence of one language onto another by different kinds of borrowing, which means that the language contact is a complex of closely intertwined linguistic and non-linguistic (cultural) phenomena. The Northwestern part of Croatia represented in the past an example of multilingualism and language contact. During the second half of the 18th century there were three languages in use: Croatian (Kajkavian dialect), Latin and German. The Kajkavian dialect was the language of everyday communication, but also of civil-legal contracts, of royal instructions and other official documents. By the end of the 18th century the German language took over the function of Latin as language of communication, education and science in the Habsburg Empire. One of the results of Austrian-Croatian language contact during the end of the 18th and in the 19th century is so-called social bilingualism. The Habsburg legacy, apart from the language contact documented in many loanwords and communication paradigms that are still in everyday use in the Northwestern Croatia, is abundantly reflected in the culture of everyday life of urban centres as well.